Implementasi Pendekatan Deep Learning dalam Pembelajaran Bahasa Indonesia di SDN Karangasem 1 - Sri Lestari; Endang Fauziati; Laili Etika Rahmawati (LPPM Institut Pendidikan Nusantara Global, 2026)
The importance of improving the quality of Indonesian language instruction in elementary schools has led to the adoption of more innovative and contextual deep learning approaches. The purpose of this study is to describe the implementation of the deep learning approach in Indonesian language instruction using infographic materials in elementary schools and to analyze its impact on the development of students’ competencies. The study employed a qualitative approach using a case study design conducted at SD Negeri Karangasem 1. Data were collected through observation, interviews, and documentation, then analyzed descriptively to depict the learning process in depth. The results indicate that the implementation of the deep learning approach in infographic-based materials unfolds through learning stages emphasizing meaningful understanding, mindful learning, and a joyful learning environment. This process encourages students to actively understand, analyze, and present information in the form of simple infographics. Furthermore, this learning approach has led to improvements in students’ literacy skills, critical thinking, creativity, and independent learning. The study’s conclusion indicates that the deep learning approach is effective in supporting more active, meaningful, and competency-oriented Indonesian language learning for elementary school students.